Morgan's canon is not evidence. (22nd January 2018) - Samuel, Steven; Clayton, Nicola
Abstract: Mahr & Csibra's (M&C's) account of the communicative function of episodic memory relies more heavily on the case against episodic memory in nonhumans than their description suggests. Although the communicative function of episodic memory may be accurate as it pertains to human behaviour, we question whether Morgan's canon is a suitable foundation on which to build theories of supposedly human-specific traits.